2014
DOI: 10.1186/1471-2164-15-406
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression between functionally specialized polyps of the colonial hydrozoan Hydractinia symbiolongicarpus (Phylum Cnidaria)

Abstract: BackgroundA colony of the hydrozoan Hydractinia symbiolongicarpus comprises genetically identical yet morphologically distinct and functionally specialized polyp types. The main labor divisions are between feeding, reproduction and defense. In H. symbiolongicarpus, the feeding polyp (called a gastrozooid) has elongated tentacles and a mouth, which are absent in the reproductive polyp (gonozooid) and defensive polyp (dactylozooid). Instead, the dactylozooid has an extended body column with an abundance of sting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 68 publications
2
47
0
Order By: Relevance
“…S1), a Wnt antagonist (Guder et al ; Augustin et al ), are significantly up‐regulated in non‐reproductive polyps of P. carnea, with little to no expression detected by RNA‐Seq in the reproductive polyps and adult medusae (Table S5). Similarly, in Hydractinia symbiolongicarpus , DE analyses of RNA‐Seq data between several polyp types revealed that reproductive polyps (gonozooids) also lack dkk1/2/4 expression (Sanders et al ). Thus down‐regulation of this Wnt antagonist is correlated with hydrozoan gonophore development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1), a Wnt antagonist (Guder et al ; Augustin et al ), are significantly up‐regulated in non‐reproductive polyps of P. carnea, with little to no expression detected by RNA‐Seq in the reproductive polyps and adult medusae (Table S5). Similarly, in Hydractinia symbiolongicarpus , DE analyses of RNA‐Seq data between several polyp types revealed that reproductive polyps (gonozooids) also lack dkk1/2/4 expression (Sanders et al ). Thus down‐regulation of this Wnt antagonist is correlated with hydrozoan gonophore development.…”
Section: Resultsmentioning
confidence: 99%
“…This assembly was annotated following the methods described previously by Sanders et al (). Gene Ontology (GO) terms were added with Blast2GO (Conesa et al ; Götz et al ), using the BLASTX algorithm and a significance threshold of 1E −03 to search against NCBI's non‐redundant (NR) protein database.…”
Section: Methodsmentioning
confidence: 99%
“…Colonial hydroids, siphonophores, and sea pens all have common gastrovascular cavities, and therefore have a level of module dissociation similar to phylactolaemates. Despite this, these taxa can be highly polymorphic, possessing polyps specialized for reproduction, defence, feeding, colony structure, and asexual propagation (Table ) (Cartwright et al, ; Cartwright, ; Dunn, ; Dunn & Wagner, ; Williams et al, ; Sanders et al, ). By contrast, scleractinian corals have a wide range of modular dissociation: polyps may be completely separated by the skeleton, share an overlying tissue (cenosarc), or may possess gastrovascular connections (coelenteric canals) through voids in the skeleton (Swain et al, ).…”
Section: Development Of Polymorphismmentioning
confidence: 99%
“…symbiolongicarpus RNA-Seq data [45] in conjunction with a draft genome assembly for a male strain, 291-10 [30] . From these mRNA and genomic sequences we identified two Eef1a alleles.…”
Section: Identification Of Hydractinia Eef1a and Parental Genotypingmentioning
confidence: 99%